Skate Life: Re-Imagining White Masculinity - Yochim, Emily C. (Technologies of the Imagination: New Media in Everyday Life, 2010)
Skate Life examines how young male skateboarders use skate culture media in the production of their identities. Emily Chivers Yochim offers a comprehensive ethnographic analysis of an Ann Arbor, Michigan, skateboarding community, situating it within a larger historical examination of skateboarding's portrayal in mainstream media and a critique of mainstream, niche, and locally produced media texts (such as, for example, Jackass, Viva La Bam, and Dogtown and Z-Boys). The book uses these elements to argue that adolescent boys can both critique dominant norms of masculinity and maintain the power that white heterosexual masculinity offers. Additionally, Yochim uses these analyses to introduce the notion of ""corresponding cultures,"" conceptualizing the ways in which media audiences both argue with and incorporate mediated images into their own ideas about identity. In a strong combination of anthropological and media studies approaches, Skate Life asks important questions of the literature on youth and provides new ways of assessing how young people create their identities.